Biological maturation, training load, and injury risk in youth soccer: An integrative review on performance, exercise-induced adaptations, and safe sport development strategies in young athletes (Research, Society and Development, 2026)
This integrative review aimed to analyze the influence of biological maturation on training load prescription and injury risk in youth soccer athletes. The literature search was conducted in the PubMed, SciELO, and LILACS databases, including studies published between 2015 and 2025, with samples composed of male athletes from the U-11 to U-23 categories. A total of 31 studies were included, addressing physiological, biomechanical, and perceptual aspects related to maturational stage. The findings indicate that maturation significantly impacts neuromuscular responses, training adaptations, perceived exertion, and injury susceptibility. The circa-PHV period was identified as a critical window, requiring strict load management and individualized exercise protocols. Strategies such as bio-banding, maturational classification, and load adjustments based on both subjective and objective indicators proved effective in mitigating risks and optimizing long-term athletic development. It is concluded that considering maturational stage is essential for safe and effective training prescription and should replace approaches based solely on chronological age in youth soccer contexts.